Dari Limbah Menjadi Solusi: Inovasi Material Sisa Industri untuk Pengolahan Seng (Zn) - Aldo Geo Frengky Saragih; Anggun Maharani; Elit Manaman Gulo; Hotma Br Butar Butar; Mutia Patmasari Batubara; Sarnika Simbolon; Iis Siti Jahro (Lembaga Pengembangan Kinerja Dosen, 2025)
Zinc (Zn) is one of the most common heavy metal contaminants found in industrial wastewater and solid residues such as slag, electroplating waste, and metal ash. At excessive concentrations, Zn can cause environmental disturbances, including toxicity to aquatic organisms, disruption of microbial activity, and groundwater contamination. Long-term exposure may also lead to bioaccumulation and potential health risks to humans. This article presents a comprehensive literature review that discusses the chemical properties of Zn, its environmental behavior, and the development of recent treatment technologies within the last five years. Several techniques, including adsorption using modified or composite materials, biosorption utilizing microalgae and agricultural biomass, as well as solidification–stabilization with amendment agents such as biochar or iron-sulfide compounds, are evaluated and compared. The literature indicates that no single treatment method is universally effective for all waste types; therefore, hybrid or integrated treatment systems are considered more efficient and sustainable. Based on the reviewed evidence, this study proposes an engineering concept that emphasizes environmental safety, cost-effectiveness, and industrial applicability.